Exploring the memory: existing activity-dependent tools to tag and manipulate engram cells - Pang, Bo; Wu, Xiaoyan; Chen, Hailun; Yan, Yiwen; Du, Zibo; Yu, Zihan; Yang, Xiai; Wang, Wanshan; Lu, Kangrong (Frontiers in Cellular Neuroscience, 2024)
The theory of engrams, proposed several years ago, is highly crucial to understanding the progress of memory. Although it significantly contributes to identifying new treatments for cognitive disorders, it is limited by a lack of technology. Several scientists have attempted to validate this theory but failed. With the increasing availability of activity-dependent tools, several researchers have found traces of engram cells. Activity-dependent tools are based on the mechanisms underlying neuronal activity and use a combination of emerging molecular biological and genetic technology. Scientists have used these tools to tag and manipulate engram neurons and identified numerous internal connections between engram neurons and memory. In this review, we provide the background, principles, and selected examples of applications of existing activity-dependent tools. Using a combination of traditional definitions and concepts of engram cells, we discuss the applications and limitations of these tools and propose certain developmental directions to further explore the functions of engram cells.